Electrochemical Nonenzymatic Acetone Sensing: A Novel Approach of Biosensor Platform Based on CNT/CuO Nanosystems - Mithra Geetha (14151807) (2023)
A promising approach for noninvasive medical diagnosis may be to measure the VOCs produced by metabolic changes or pathological disorders in human sweat, such as measuring the acetone levels in the presence of diabetes. Acetone is a by‐product of fat catabolism and serves as an indicator of ketosis and diabetes. The measurement of acetone may be used instead of glucose monitoring. Current research aims to develop and improve noninvasive methods of detecting acetone in sweat that are accurate, sensitive, and stable. The carbon nanotubes (CNTs)–copper oxide (CuO) nanocomposite (NC) improves direct electron transport to the electrode surface in this study. The complex‐precipitation method is used to make this NC. X‐ray diffraction (XRD) and scanning electron microscopy (SEM) are used to investigate the crystal structure and morphology of the prepared catalyst. Using cyclic voltammetry (CV) and amperometry, the electrocatalytic activity of the as‐prepared catalyst is evaluated. The electrocatalytic activity in artificial sweat solution is examined at various scan rates and acetone concentrations. The detection limit of the CNTs‐CuO NC catalyst is 0.05 mm, with a sensitivity of 16.1 mA cm−2 µm−1 in a linear range of 1–50 mm. Furthermore, this NC demonstrates a high degree of selectivity for various biocompounds found in sweat, with no interfering cross‐reactions from these species. The CNT‐CuO NC, as produced, has good sensitivity, rapid reaction time (2 s), and stability, indicating its potential for acetone sensing. Other Information Published in: Macromolecular Symposia License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/masy.202200150